Design and Evaluation of a Personal Diffusion Battery - Vosburgh, Donna J H (Aerosol science and technology : the journal of the American Association for Aerosol Research, 2013)
A four-stage personal diffusion battery (pDB) was designed and constructed to measure submicron particle size distributions. The pDB consisted of a screen-type diffusion battery, solenoid valve system, and electronic controller. A data inversion spreadsheet was created to solve for the number median diameter (NMD), geometric standard deviation (GSD), and particle number concentration of unimodal aerosols using stage number concentrations from the pDB combined with a handheld condensation particle counter (pDB+CPC). The inversion spreadsheet included particle entry losses, theoretical penetrations across screens, the detection efficiency of the CPC, and constraints so the spreadsheet solved to values within the pDB range. Size distribution parameters (NMD, GSD, and number concentration) measured with the pDB+CPC with inversion spreadsheet were within 25% of those measured with a scanning mobility particle sizer (SMPS) for 5 of 12 polydisperse combustion aerosols. For three tests conducted with propylene torch exhaust, the pDB+CPC with inversion spreadsheet successfully identified that the NMD was smaller than the constraint value of 16 nm. The ratio of the nanoparticle portion of the aerosol compared to the reference (Rnano) was calculated to determine the ability of pDB+CPC with inversion spreadsheet to measure the nanoparticle portion of the aerosols. The Rnano ranged from 0.87 to 1.01 when the inversion solved and from 0.06 to 2.01 when the inversion solved to a constraint. The pDB combined with CPC has limited use as a personal monitor but combining the pDB with a different detector would allow for the pDB to be used as a personal monitor